Fast Sodium‐Ion Conductivity in Supertetrahedral Phosphidosilicates. Issue 21 (2nd May 2018) - Haffner, Arthur; Hatz, Anna‐Katharina; Moudrakovski, Igor; Lotsch, Bettina V.; Johrendt, Dirk
Abstract: Fast sodium‐ion conductors are key components of Na‐based all‐solid‐state batteries which hold promise for large‐scale storage of electrical power. We report the synthesis, crystal‐structure determination, and Na + ‐ion conductivities of six new Na‐ion conductors, the phosphidosilicates Na19 Si13 P25, Na23 Si19 P33, Na23 Si28 P45, Na23 Si37 P57, LT ‐NaSi2 P3 and HT ‐NaSi2 P3, based entirely on earth‐abundant elements. They have SiP4 tetrahedra assembled interpenetrating networks of T3 to T5 supertetrahedral clusters and can be hierarchically assigned to sphalerite‐ or diamond‐type structures. 23 Na solid‐state NMR spectra and geometrical pathway analysis show Na + ‐ion mobility between the supertetrahedral cluster networks. Electrochemical impedance spectroscopy shows Na + ‐ion conductivities up to σ (Na + )=4×10 −4 S cm −1 . The conductivities increase with the size of the supertetrahedral clusters through dilution of Na + ‐ions as the charge density of the anionic networks decreases. Abstract : Networks of large supertetrahedral phosphidosilicate clusters facilitate fast Na + ‐ion conduction in the new compounds Na23 Si9 n +19 P12 n +33 which are entirely based on earth‐abundant elements. The conductivities increase with the size of the supertetrahedral clusters, as a result of dilution of Na + ions, up to 4×10 −4 S cm −1 which is comparable to other fast solid ionic conductors.